Development of Corporate Strategy for China Oceanwide in Indonesia - Ying, Xie; Wicaksono, Agung (The Indonesian Journal of Business Administration, 2017)
Abstract - Indonesia is now one of the most appealing markets for coal-fired electricity generation. In order to support and sustain Indonesia's economic growth, President Jokowi plans to increase the production of electricity to 35 GW over the next five years. Placed in an increasingly integrated and energy-hungry region, Indonesia's largest economy is definitely one to watch for electricity investors. Therefore, it is an attractive opportunity for independent power producers (IPPs), either private or foreign investors. The huge power generation construction plan has attracted the attention of the world's power giants, including groups from Europe, Korea, Japan, China, one of which is China Oceanwide holding group (Oceanwide) who is a mature coal-fired electricity generation investor. This project is to identify how Oceanwide can develop in the host country Indonesia, how should Oceanwide compete with competitors from Local, Europe, Korea, Japan, even from China and overcome or minimize the investment risks as a new entry FDI company.It outlines the related strategic theory, the business issue exploration, the business solution, the benchmarks’ experience, such as GE, Siemens. It analyzes Oceanwide’s external environment and internal environment by the business strategies such as the selection and evaluation of SWOT analysis, Porter’s five forces model. This project proposed Market entry strategy, G2G Model, Differentiation strategy, risk transfer strategy, Merger and acquisition strategy and Pluralistic Strategy for the development of Oceanwide. Oceanwide right now is applying G2G model, it will work for Oceanwide’s development.Key words: Business strategy, FDI, IPP, G2G Model, Development